Isoconversional Approach to Evaluating the Hoffman-Lauritzen Parameters (U and Kg) from the Overall Rates of Nonisothermal Crystallization - Vyazovkin, Sergey; Sbirrazzuoli, Nicolas (Macromolecular rapid communications., 2004)
An equation has been derived that correlates the temperature coefficient of the growth rate with the temperature dependence of the effective activation energy of the overall crystallization rate, which can be measured by differential scanning calorimetry. The dependence is evaluated by using an advanced isoconversional method and is parameterized in terms of the Hoffman–Lauritzen equation. The parameters obtained for the nonisothermal crystallization of the poly(ethylene terephthalate) melt are consistent with the parameters reported for isothermal crystallization. The fit of the equation derived here is shown for data corresponding to the dependence of the effective activation energy on average temperature (fit = solid line).